Do instagram fan pages develop consumer–brand relationships? Evidence from the telecommunications industry - Hazem Rasheed Gaber (Taylor & Francis Group, 2021)
Instagram’s growth has drawn the interest of many corporations that are searching for new ways to boost their customer relationships. Given the rapid adoption of Instagram marketing and the inadequate research in that field, the objective of this paper is to examine whether “following” brands on Instagram fan pages enhances consumer–brand relationship from the consumer perspective. The data were collected from consumers who follow Instagram fan pages of the four telecommunication companies that are operating in Egypt using an online questionnaire. The telecommunication industry is one of the major industries that rely heavily on Instagram marketing in Egypt. The results indicated that fan page following positively and significantly influences the consumers’ brand love and sense of brand community. Also, the findings indicated the consumers’ brand love positively impacts consumers’ purchase intention and word of mouth. Finally, it showed that consumers’ sense of brand community impacts their purchase intention and word of mouth positively. This article contributes theoretically by expanding the focus of brand community literature to fan pages as an innovative form of social media brand communities. Furthermore, it provides recommendations to practitioners to follow when managing Instagram fan pages.